Interpersonal Communication Between Shadow Teachers and Students with Special Needs in Inclusive Schools - Putri, Merlinda Sayidatina Aisyah; Sumardjijati (Informasi, 2026)
This study aims to analyze interpersonal communication between students with special needs and shadow teachers in inclusive schools, specifically at State Junior High School 31 Surabaya. Using a qualitative descriptive approach with in-depth interviews and literature review techniques, this study involved six informants: five ninth-grade students with special needs and one special shadow teacher serving as the inclusion coordinator with a background in Guidance and Counseling. Data analysis was based on DeVito’s humanistic approach theory, which encompasses openness, empathy, supportiveness, positiveness, and equality. The results indicate that the shadow teacher successfully established effective interpersonal communication by applying these five humanistic aspects, characterized by consistent informal communication, acting as a problem solver, using adaptive teaching methods, Sensitivity to students’ emotional conditions, and implementing differentiated instruction. The interpersonal communication established has a positive impact on the psychological condition and learning motivation of students with special needs. On the other hand, the study also identified four communication barriers: physical barriers in the form of classroom noise; physiological barriers due to students’ biological limitations; psychological barriers in the form of social anxiety; and semantic barriers resulting from the complexity of the subject matter.